Endividamento público: o caso de São Paulo - Santos, Gilton Carneiro dos (1983)
This dissertation intends to analyze the evolution publicdebt of te Stateof são Paulo in the period 1892/1980, with emphasis on more recent years (1975/80). An approach basden the theory of Public Finance is used and it attempts to connect the debt of Direct Administration with changes the National Tax System. It also intends to show the contribution of public debt as an alternative source or funds to State of São Paulo and the burden of that policy. The composition ot debt and its legal limitations are also examined.